2007
DOI: 10.1068/d76j
|View full text |Cite
|
Sign up to set email alerts
|

The Performative Landscape of Going-To-Work: On the Edge of a Jewish Ultraorthodox Neighborhood

Abstract: Following recent insights into performativity and space, I explore the widespread routine of going-to-work as a capitalist ritual. Going-to-work produces a powerful yet ordinary, unspectacular landscape, whose performativity is fourfold: the compatibility of the material form and human use of it; the movements of people and the clothes they wear; the variety of individual practices of going-to-work; and the timing and spacing of this collective ritual. Generally, going-to-work is performative, because it trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
(50 reference statements)
1
13
0
Order By: Relevance
“…As these studies have demonstrated, the stories commuters tell about their experiences helps make more explicit the personal, emotional side of commuting and automobile travel. Individual narratives allow us to perceive how those who do it understand driving to work not as an undesirable or empty activity, but rather as something complex and meaningful and important (Blumen 2007).…”
Section: Positive Utilitymentioning
confidence: 99%
“…As these studies have demonstrated, the stories commuters tell about their experiences helps make more explicit the personal, emotional side of commuting and automobile travel. Individual narratives allow us to perceive how those who do it understand driving to work not as an undesirable or empty activity, but rather as something complex and meaningful and important (Blumen 2007).…”
Section: Positive Utilitymentioning
confidence: 99%
“…Three groups are typically considered disadvantaged in the labor market, namely, Palestinian Arabs, Sephardic Jews, and females. With the majority of Palestinian Arabs continuing to be employed primarily in blue-collar jobs, such as construction and manufacturing (Blumen, 2007), the pay of male salaried employees continues to be over 20% higher than that of females on average (Israel Ministry of Industry and Trade, 2007) and higher unemployment rates for females and Arabs relative to male Jews (9.5% and 12.8% vs. 8.3%, respectively); concerns regarding employment and income disparities remain major issues in the Israeli political landscape.…”
Section: Israelmentioning
confidence: 99%
“…From this perspective, it looks as if a new kind of spatiality might appear which may bring about motion between those two spaces (Blumen 2007a(Blumen , 2007b. From this perspective, it looks as if a new kind of spatiality might appear which may bring about motion between those two spaces (Blumen 2007a(Blumen , 2007b.…”
Section: Discussionmentioning
confidence: 99%
“…Guggenheim and O. Taubman -Ben-Ari even endanger the stringent social norms regarding the above-mentioned division of private-public spatialities (Blumen 2002). Although studies have explored various aspects of women's mobility around the world, to the best of our knowledge, only few dealt specifically with ultraorthodox women (Blumen 2002(Blumen , 2007a(Blumen , 2007b. While restricting space is often considered a crucial indicator of the political and social insignificance of women in a society (Fenster 2005;Moss and Falconer Al-Hindi 2008), specific cultural norms may shed light on other possible explanations for this social phenomenon.…”
Section: Introduction: Women Road Users In the Ultraorthodox Communitymentioning
confidence: 99%